Unilateralism and Bilateralism in the Restrictions on Worship in Italy During the Pandemic (Stato, Chiese e pluralismo confessionale, 2022)
TABLE OF CONTENTS: 1. Introduction - 2. The Italian constitutional framework and the principle of pactional bilaterality - 3. Restrictions on worship after the first phase of the pandemic - 4. The impact of the Protocols on the system of sources of Ecclesiastical law - 5. Conclusions. From bilateralism to “loyal cooperation”?ABSTRACT: This contribution presents an investigation through the legal sources on which the restrictions on worship were imposed with the aim of verifying whether, and how, the normative management of the pandemic affected the bilateralism that characterizes relations between the State, the Catholic Church, and the various religious denominations. The main point of reference for the analysis will be the contents of the decree-laws, the Prime Ministerial Decrees (DPCM) and their annexes and the aim is to verify, in the context of the peculiar Italian ecclesiastical policy, the differences in treatment between the Catholic Church, religions with an agreement and religions without an agreement.